What Determines Village Autonomy in Indonesia? A Case of Villages in Sleman Regency - Pratolo, Suryo; Atmaja, Nandhika Ristyawardani Surya; Sofyani, Hafiez (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aims to examine the influence of community participation and the competence of village apparatus on village fund management and village autonomy. The role of the village fund management as an intervening variable was also tested. This study was conducted in the regional government in the Sleman Regency, Yogyakarta Special Province, Indonesia. The samples were selected based on the cluster random sampling technique i.e. 30 villages in Sleman Regency. The survey was undertaken from September 2018 to January 2019. The respondents consisted of village heads, village secretaries, and village treasurers. To test the hypothesis, a multiple linear regression approach was applied. The results demonstrate that the community participation directly affects the village fund management and it has an indirect influence on the village autonomy through the village fund management as the intervening variable. Meanwhile, the competence of village government officials only directly affects the management of village funds.